Metabolic complications of obesity in children and adolescents - Hyunjin Park; Jung Eun Choi; Seunghee Jun; Hyelim Lee; Hae Soon Kim; Hye Ah Lee; Hyesook Park (The Korean Pediatric Society, 2024)
The global prevalence of childhood and adolescent obesity, exacerbated by the coronavirus disease 2019 pandemic, affects school-aged children and preschoolers. Early-onset obesity, which carries a high risk of metabolic complications, may contribute to a lower age at the onset of cardiovascular disease. As metabolic diseases such as diabetes, dyslipidemia, and nonalcoholic fatty liver disease observed in adulthood are increasingly recognized in the pediatric population, there is an emphasis on moving disease susceptibility assessments from adulthood to childhood to enable early detection. However, consensus is lacking regarding the definition of metabolic diseases in children. In response, various indicators such as the pediatric simple metabolic syndrome score, continuous metabolic syndrome score, single-point insulin sensitivity estimator, and fatty liver index have been proposed in several studies. These indicators may aid the early detection of metabolic complications associated with pediatric obesity, although further validation studies are needed. Obesity assessments are shifting in perspective from visual obesity to metabolic health and body composition considerations to fill the gap in health impact assessments. Sarcopenic obesity, defined as the muscle- to-fat ratio, has been proposed in pediatric populations and is associated with metabolic health in children and adolescents. The National Health Screening Program for Children in Korea has expanded but still faces limitations in laboratory testing. These tests facilitate timely intervention by identifying groups at a high risk of metabolic complications. Early detection and intervention through comprehensive health screening are critical for mitigating long-term complications of childhood obesity.